Electrochemical codeposited polypyrrole–tungsten oxide composite materials with wide potential windows. Issue 10 (4th May 2020) - Bai, Minghua; Li, Yidi; Liu, Rui; Yu, Zhan; Wang, Ying; Zhao, Zhen
Abstract: The three‐dimensional morphology has sufficient interface contact and can be in favor of the electronic transport process. In this work, the demand for high‐performance electrodes such as energy storage devices has been designed. Polypyrrole and tungsten oxide composite materials (PPy‐WO3 ) have been synthesized by cyclic voltammetry (CV) technology at −0.6 to 0.9 V versus saturated calomel electrode (SCE) for 20 cycles. The PPy‐WO3 20 mV/s, PPy‐WO3 60 mV/s, and PPy‐WO3 120 mV/s electrodes have been prepared by CV technology at sweep rates of 20, 60, and 120 mV/s. The influences of scan rate on morphologies and charge storage properties of the composites are discussed. Among them， a three‐dimensional flake structure for PPy‐WO3 20 mV/s with a size of up to several micrometers was synthesized. PPy‐WO3 20 mV/s composites as electrode materials exhibit a wide charge storage potential window of 1.4 V (between −0.9 and 0.5 V vs. SCE) and a specific capacitance of 145.13 F/g at 1 mA/cm 2 . Moreover, the long‐term stability of PPy‐WO3 20 mV/s and PPy has been investigated in 5 M LiCl aqueous electrolyte. The stability of the materials can be improved by inorganic and organic composites. Abstract : Three‐dimensional nanosheets of PPy were directed through electrocodeposition with WO3. The charge storage potential window of the PPy‐WO3 electrode was 1.4 V.